The standards of logopedic treatment in case of oncological patients in scope of head and neck, treated in the Gliwice branch Oncology Centre - Gniezdzia – Buc, Izabela; Hamerlińska, Agnieszka (Journal of Education, Health and Sport, 2017)
The paper discusses the standards of speech therapy to oncology patients in the scope of head and neck, treated in the Gliwice branch Oncology Centre. All the observations were based on the analisis of both medical and speech therapy literature as well as on the examinations carried out during the neuro speech therapist’s professional duties at the 1 st. Clinic of Radiotherapy and Chemotherapy as well as Oncologic and Reconstructive Surgery Clinic Oncology-Institute Gliwice Division. This study presents knowledge on logopedic rehabilitation conducted even before the surgery, after reconstructive surgery during radiotherapy and after its completion. Serious surgeries of tumour do not only result in anatomical changes in the oral cavity but also cause dysphagia, change the quality of speech, the way of breathing and negatively affect the patient’s assessment of life and weaken their sense of security. The present article is an attempt of showing general standards of treatment towards oncological patients including speech therapy examination, diagnosis and therapy. A modern speech therapist does not only deal with therapy of speech defects and correct communication but acts within the fields of education, psychology and medicine also oncological. As a result further observations and logopedic diagnosis should be made to provide universal standards of logopedic treatment for oncological patients in the scope of head and neck in order to create a new subpecialization in the field of speech therapy-oncologopedic.